Administrative and legal basis of strategic planning in the public sector - Leschishin, Ruslan (Actual problems of law (Aktual'ni problemi pravoznavstva), 2021)
Strategic planning is a key vector of modern state policy of Ukraine aimed at solving the problems of sustainable socio-economic development and ensuring the national security of Ukraine. The introduction of the Draft Law of Ukraine «On State Strategic Planning» in the Parliament marked a new stage in the legal regulation of state strategic planning. The article substantiates the need to create effective institutional and legal mechanisms for strategic planning at the national and regional levels to ensure national interests and achieve strategic national priorities. The paper analyzes the experience of implementing the state system of strategic planning in Ukraine, identifies the main problems of creating a targeted system of strategic planning in the country, considers the hierarchy of strategic documents of developed countries, presents the logic and methodology of formation as the main long-term strategic document.Taking into account the research goals and objectives, the main provisions of the legislation in the field of strategic planning, national security and socio-economic development of the state are analyzed. The conclusion is formulated that strategic planning as part of public administration determines the main directions and priorities of socio-economic policy and national security of Ukraine. practice-oriented scientific and methodological approaches that meet the basic principles of organization and functioning of the strategic planning system.